The Search as Learning Spaceship: Toward a Comprehensive Model of Psychological and Technological Facets of Search as Learning - von Hoyer, Johannes; Hoppe, Anett; Kammerer, Yvonne; Otto, Christian; Pardi, Georg; Rokicki, Markus; Yu, Ran; Dietze, Stefan; Ewerth, Ralph; Holtz, Peter (Frontiers in Psychology, 2022)
Using a Web search engine is one of today’s most frequent activities. Exploratory search activities which are carried out in order to gain knowledge are conceptualized and denoted as Search as Learning. In this paper, we introduce a novel framework model which incorporates the perspective of both psychology and computer science to describe the search as learning process. The main entities of the model are the learner who is surrounded by a specific learning context, the interface that mediates between the learner and the information environment, the information retrieval backend which manages the processes between the interface and the set of Web resources, that is the collective Web knowledge represented in resources of different modalities. At first, we provide an overview of the current state of the art with regard to the five main entities of our model, before we outline areas of future research to improve our understanding of search as learning processes.